2021
DOI: 10.3390/metabo11100656
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Marathon-Induced Metabolic Changes Using 1H-NMR Metabolomics

Abstract: Although physical activity is a health-promoting, popular global pastime, regular engagement in strenuous exercises, such as long-distance endurance running races, has been associated with a variety of detrimental physiological and immunological health effects. The resulting altered physiological state has previously been associated with fluctuations in various key metabolite concentrations; however, limited literature exists pertaining to the global/holistic metabolic changes that are induced by such. This in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…In the current study, greater deceases in leucine, isoleucine, and valine, at POST compared to PRE, regardless of treatment, suggest that BCAA were used as an energy source during aerobic exercise regardless of glycogen content. Reductions in circulating BCAA are in agreement with previous studies assessing the change in circulating metabolites after aerobic exercise compared to resting fasted conditions [20,21,26,27]. However, though each BCAA decreased in POST compared to PRE aerobic exercise in the current study, downstream BCAA metabolites, such as 3-methyl-2-oxovalerate, 4-methyl-2-oxopentanoate, and 3-hydroxyisobutyrate, had greater increases in LOW compared to AD.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, greater deceases in leucine, isoleucine, and valine, at POST compared to PRE, regardless of treatment, suggest that BCAA were used as an energy source during aerobic exercise regardless of glycogen content. Reductions in circulating BCAA are in agreement with previous studies assessing the change in circulating metabolites after aerobic exercise compared to resting fasted conditions [20,21,26,27]. However, though each BCAA decreased in POST compared to PRE aerobic exercise in the current study, downstream BCAA metabolites, such as 3-methyl-2-oxovalerate, 4-methyl-2-oxopentanoate, and 3-hydroxyisobutyrate, had greater increases in LOW compared to AD.…”
Section: Discussionsupporting
confidence: 92%
“…NAM is essential for cardiovascular health through enhancing myocardial homeostasis and inhibiting cardiomyocyte apoptosis 27 . Excessive exercise is attributed to myocardial ischemia and hypoxia, leading to significantly decreased NAM and exercise-induced fatigue in rats 28 , 29 . In our study, significantly decreased NAM during acute high-intensity exercise was found, suggesting reduced exercise-induced NAM of myocardium might induce cardiac pathological damage.…”
Section: Discussionmentioning
confidence: 99%
“…To remove macromolecules such as proteins from the serum samples, which could potentially interfere with the 1 H-NMR analysis, 100 µL of each serum sample was first filtered using pre-rinsed centrifugal filter units (10 kDa pore size). Following this, the serum samples were prepared using a miniaturized 1 H-NMR method, as described previously [ 50 ]. This involved adding NMR buffer solution to the serum samples and transferring them to 2 mm NMR tubes.…”
Section: Methodsmentioning
confidence: 99%
“…Each brain sample analyzed yielded an NMR spectrum with a width of 12,000 Hz (24.0 ppm), while each serum sample’s spectrum had a width of 6000 Hz (12 ppm). Data pre-processing was performed using Bruker Topspin (V3.5) (Bruker, Billerica, MA, USA), the technicalities of which have been described previously [ 50 ]. Further data analysis and processing were carried out using Bruker Amix (V3.9.14) (Bruker, Billerica, MA, USA) and consisted of normalizing all peaks to TSP and dividing the spectrum into bins with a width of 0.02 ppm.…”
Section: Methodsmentioning
confidence: 99%